Bilingue, Superhéroe = Bilingual, Super Hero - Argueta, Jorge (Piñata Books, Arte Público Press, 2024)
"Award-winning author Jorge Argueta once again pens a poetic story for kids that touches on ordinary lives that are extraordinary, in this case a boy known as "Bilingual" with super-hero skills in both English and Spanish who loves to help those around him"--